The Prevalence of Oral Leukoplakia: Results From a Romanian Medical Center - Ramona Vlad; Irinel Panainte; Alexandra Stoica; Monica Monea (European Scientific Journal, ESJ, 2016)
The aim of our study is to measure the prevalence of oral leukoplakia in a selected population group in association with variables as gender, age, smoking and alcohol intake. The mucosal lesions were diagnosed and classified according to internationally accepted criteria. Results showed that the majority of oral leukoplakia belonged to homogenous type and only o few were non-homogenous, with a prevalence of 3.32% 1.10% respectively, a difference that was statistically significant. The most frequent location of oral leukoplakia was the oral mucosa of the cheek, lower lip, tongue and floor of the oral cavity. Our conclusion was that oral leukoplakia occurred more frequently in men over the age of 45 and smoking and alcohol abuse were positive correlated factors.